The Influence of Room Colors in A House for Its Occupants - Hendrassukma, Dila (Bina Nusantara University, 2016)
Home was a place where each individual could go after doing various routine activities. Residential interior design would support the quality of life of its occupants. The majority of the population of Indonesia, especially in Jakarta, had been aware of the importance of design interior of their homes properly. However, the selection of interior elements of color that was supporting the smoothness of the activities in a room was not considered as whole. The research objective was to analyze a great color for every room in the home based on the theory and the psychology of color. This article was expected to be a guide for those who will design an interior room. The method used was qualitative method in the form of observation and study of literature. Results of the study is the choice of a suitable color that fit in any room home, such as the living room, bedroom, kitchen, and bathroom can maximize the function of the room for the occupants.